15‐Lipoxygenase Promotes Chronic Hypoxia‐Induced Phenotype Changes of PASMCs Via Positive Feedback‐Loop of BMP4. Issue 7 (July 2015) - Yu, Xiufeng; Wei, Liuping; Lu, Ping; Shen, Tingting; Liu, Xia; Li, Tingting; Zhang, Bo; Yu, Hao; Zhu, Daling
Abstract : Our laboratory has previously demonstrated that 15‐lipoxygenase (15‐LO)/15‐hydroxyeicosatetr‐aenoic acid (15‐HETE) is involved in hypoxic pulmonary arterial hypertension (PAH). Phenotypical alterations of vascular smooth muscle cells are considered to be an important stage in the development of PAH, whereas the underlying mechanisms and signaling systems are still unclear. Here, we determined the contribution of 15‐LO/15‐HETE signaling in the hypoxia–induced phenotype changes of pulmonary arterial smooth muscle cells (PASMCs). To accomplish this, cellular and molecular changes in pulmonary vascular remodeling were detected in PAH patients and rats exposed to hypoxia. We found that the hypoxia‐induced alterations in PASMCs phenotypes were reversed by the inhibition of 15‐LO/15‐HETE or inhibition of BMP4/BMPRI. Hypoxia‐induced 15‐LO1/2 expression in rat PASMCs was significantly abolished by small interfering RNA targeted at BMP4. Meanwhile, BMP4/BMPRI‐15‐LO/15‐HETE had a positive feedback mechanism. Furthermore, ERK and p38MAPK act as the downstream of the 15‐LO/15‐HETE‐BMP4/BMPRI signaling. Our results suggest that chronic hypoxia promotes phenotypical alterations of PASMCs due to the interaction between 15‐LO/15‐HETE and BMP4/BMPRI. Our study reveals a novel mechanism of hypoxia‐induced pulmonary vascular remodeling and suggested new therapeutic strategies for the targeting of 15‐LO/15‐HETE and BMP4/BMPRI in PAH treatment. J. Cell. Physiol. 230: 1489–1502, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company